2013
DOI: 10.1111/jicd.12076
|View full text |Cite
|
Sign up to set email alerts
|

Flies and the mouth

Abstract: Oral infections caused by flies are rarely encountered in clinical practice, and consequently, there is a paucity of information in the medical and dental literature about these conditions. In the present article, we present a concise review on oral myiasis or fly-blown disease. A variety of fly species can infest the oral tissues and produce an exotic clinical picture. Oral myiasis is mainly encountered in the tropics and subtropics, but can also be encountered in the western part of the world due to the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…9,10 Also, not all microbial species within a similar clade are pathogenic to humans. Some are nonpathogenic, or only pathogenic to nonprimates and seen in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Also, not all microbial species within a similar clade are pathogenic to humans. Some are nonpathogenic, or only pathogenic to nonprimates and seen in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them attach their eggs to mosquitoes that transmit the larvae via their bites. Other flies' larvae (known as screwworms) can enter skin through bare feet or attach themselves to clothes and then burrow into the skin of the human; and some flies deposit their larvae in, on, or near a wound (11). It is suggested that the botfly Dematobia hominis does not lay the eggs directly on the host.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent literature review, Singh et al (4) described approximately 37 different fly species belonging to ten families as responsible worldwide for the onset of human myiasis and the most frequently reported were those from the family Calliphoridae, Sarcophagidae, Oestridae, Muscidae, Psychodidae, Syrphidae, Phoridae, Drosophilidae, Dryomyzidae and Gasterophilidae. Regarding oral myiasis, species that have already been reported include Cochliomyia hominivorax, Oestrus ovis, Wohlfahrtia magnifica, Chrysomya bezziana, Hypoderma (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myiasis is usually treated by Ivermectin administration, a drug that is effective against many types of parasites, in humans and other mammals. This drug eliminates parasites after their palsy and death, followed by its mechanical removal with forceps or tweezers . Furthermore, antibiotics can also be used to avoid the possibility of secondary infections .…”
Section: Introductionmentioning
confidence: 99%